Best Free Reference Web Sites: Ninth Annual List - Langan, James; Perkins, Margaret Y; Cobine, Charles J; Dunham, Christopher S; Geck, Caroline E; Meszaros, Rosemary (Reference & User Services Quarterly, 2007)
The committee has established the following criteria for nominated Web sites: * quality, depth, and usefulness of content * clear statement of the content, including any intended biases * appropriateness for the intended audience * appropriate links to other Web sites * attention to detail; absence of grammatical errors and so on * ready reference; usefulness for reference to answer specific questions * may also give a broad perspective of a particular subject * uniqueness of content * uniqueness of the resource as a whole; creativity * useful in a variety of reference settings * currency of content * links are kept up to date * update frequency is appropriate for the subject matter * authority of producer * authority and legality clearly stated * if not easily recognizable, an explanation of the history and purpose of the organization * ease of use * user-friendly design; easy navigation * good search engine * attractive; graphie design makes a good impression on thé user * easy output (printing or downloading) * customer service * contacts are responsive; e-mail addresses are correct * authority of producer * authority and legality clearly stated * if not recognizable, an explanation of the history and purpose of the organization * efficiency (note: efficiency is affected by the user's method of Internet access-dial-up access, for example, will no doubt be less efficient for all sites-and evaluators endeavored to take such differences into account) * graphics load quickly or are not so intensive as to seriously degrade access * any required plug-ins are available for easy download * reliable, speedy server; information is there when needed * appropriate use of the Web as a medium * components are well integrated (audio, video, text, and so on) * useful information is still available, even if the user does not have all the plug-ins and media components * effective use of Java, other newer technologies As in previous years, the committee worked virtually, and the process went smoothly, especially as many of the members were returning for a third or fourth year. Feb. 28, 2007 The Bill of Rights Institute, www.billofrightsinstitute.org The Bill of Rights Institute is a nonprofit organization whose mission is to teach youth "about the words and ideas of America's Founders, the liberties guaranteed in our Founding documents, and how our Founding principles continue to affect and shape a free society." Teachers (and others) can sign up for newsletters with links to lessons on the topics of Bill of Rights in the news, First Amendment in history, and landmark Supreme Court cases.